Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

Identification and Characterization of sanH and sanI Involved in the Hydroxylation of Pyridyl Residue During Nikkomycin Biosynthesis in Streptomyces ansochromogenes - Zhoujie Xie; Guoqing Niu; Rui Li; Gang Liu; Huarong Tan (Current Microbiology, 2007)

Mitochondrial and chloroplast phylogeography of Picea crassifolia Kom. (Pinaceae) in the Qinghai‐Tibetan Plateau and adjacent highlands - LIHUA MENG; RUI YANG; RICHARD J. ABBOTT; GEORG MIEHE; TIANHUA HU; JIANQUAN LIU (Molecular Ecology, 2007)
The disjunct distribution of forests in the Qinghai‐Tibetan Plateau (QTP) and adjacent Helan Shan and Daqing Shan highlands provides an excellent model to examine vegetation shifts, glacial refugia and gene flow of key species in this complex landscape region in response to past climatic oscillations and human disturbance. In this study, we examined maternally inherited mitochondrial DNA ( nad 1 intron b/c and nad 5 intron 1) and paternally inherited chloroplast DNA ( trn C‐ trn D) sequence variation within a dominant forest species, Picea crassifolia Kom. We recovered nine mitotypes and two chlorotypes in a survey of 442 individuals from 32 populations sampled throughout the species’ range. Significant mitochondrial DNA population subdivision was detected ( G ST = 0.512; N ST = 0.679), suggesting low levels of recurrent gene flow through seeds among populations and significant phylogeographical structure ( N ST > GST , P G ST = N ST = 0.093). This provides evidence for highly efficient pollen‐mediated gene flow among isolated forest patches, both within and between the QTP and adjacent highland populations. A lack of isolation to pollen‐mediated gene flow between forests on the QTP and adjacent highlands is surprising given that the Tengger Desert has been a geographical barrier between these two regions for approximately the last 1.8 million years.

Survival and integration of tissue-engineered corneal stroma in a model of corneal ulcer - Chao Zhang; Xin Nie; Dan Hu; Yuan Liu; Zhihong Deng; Rui Dong; YongJie Zhang; Yan Jin (Cell and Tissue Research, 2007)

Regulation of skeletal muscle differentiation in fibroblasts by exogenous MyoD gene in vitro and in vivo - Rui-feng Qin; Tian-qiu Mao; Xiao-ming Gu; Kai-jing Hu; Yan-pu Liu; Jin-wu Chen; Xin Nie (Molecular and Cellular Biochemistry, 2007)

Application of a Larval Medaka Assay to Evaluate the Fish Safety Level in Sagami River, Japan - Rui Liu; Takashi Kameya; Atsushi Sawai; Kohei Urano (Environmental Monitoring and Assessment, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)

pEGFP-T, a novel T-vector for the direct, unidirectional cloning and analysis of PCR-amplified promoters - Baoli Wang; Xiaoxia Li; Fang Zheng; Rui Liu; Jinxing Quan; Hui Liang; Shanyi Guo; Gang Guo; Jingyu Zhang (Biotechnology Letters, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)